Conservation of Timor Deer (Cervus timorensis) in Saobi Island Nature Reserve - Mohammad Imam Sufiyanto; Roviandri; Jamiludin Usman; Syarif Hidayatullah; Jonathan Siborutorop (Al Jahiz, 2025)
The ongoing climate change and the interests of the surrounding community in the Saobi Island Nature Reserve, make the conservation of eastern deer (cervus timorensis) in the Saobi Island Nature Reserve very important to maintain the deer population on Saobi Island. This study aims to use the Participation Action Research (PAR) method as a persuasive method in maintaining the forest population and a massive approach around Saobi Island to be able to maintain the deer population around the nature reserve with stages in the form of action plans, focus group discussions (FGD), socialization, and reflection on the activities carried out in the study. The results of this study indicate a positive impact in the form of the formation of a partner community and the emergence of various additional benefits felt during the study, in the form of social and educational activities through action plans, socialization to educational institutions on Saobi Island, especially to Islamic junior high schools (MTS) in the long term, focus group discussion forums (FGD) with the natural resource conservation center, the Conservation and Natural Resources Center, and the presence of forest rangers around the Saobi Island nature reserve. Then the reflection carried out was to create a partner community around Saobi Island whose development was continuously monitored to be able to maintain the sustainability of the existing deer and maintain the deer population on Saobi Island.